2009
DOI: 10.1124/jpet.109.151415
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Casein Kinase 1ϵ Minimally Alters Circadian Clock Period

Abstract: The circadian clock links our daily cycles of sleep and activity to the external environment. Deregulation of the clock is implicated in a number of human disorders, including depression, seasonal affective disorder, and metabolic disorders. Casein kinase 1 epsilon (CK1) and casein kinase 1 delta (CK1␦) are closely related Ser-Thr protein kinases that serve as key clock regulators as demonstrated by mammalian mutations in each that dramatically alter the circadian period. Therefore, inhibitors of CK1␦/ may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 34 publications
(46 reference statements)
7
179
0
2
Order By: Relevance
“…Together, these results suggest that both Csnk1e and Csnk1d are important for sensitivity to drugs of abuse. However, because PF-670462 only exhibits six-fold selectivity for Csnk1d over Csnk1e (Walton et al, 2009;Meng et al, 2010), it is unclear if our previous results were mediated by Csnk1d or Csnk1e (Bryant et al, 2009b;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Together, these results suggest that both Csnk1e and Csnk1d are important for sensitivity to drugs of abuse. However, because PF-670462 only exhibits six-fold selectivity for Csnk1d over Csnk1e (Walton et al, 2009;Meng et al, 2010), it is unclear if our previous results were mediated by Csnk1d or Csnk1e (Bryant et al, 2009b;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…PF-670462 was previously thought to be slightly more selective for Csnk1e over Csnk1d (Badura et al, 2007), but a recent study showed that PF-670462 was six-fold more selective for Csnk1d over Csnk1e and that PF-4800567 was 20-fold more selective for Csnk1e over Csnk1d (Walton et al, 2009). Because PF-4800567 increased MA and fentanyl sensitivity whereas PF-670462 decreased MA sensitivity, the combined results provide further evidence that Csnk1e and Csnk1d exert opposing regulatory roles on the locomotor stimulant response to drugs of abuse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations